Detection of neovascularisation in the vitreoretinal interface slab using widefield swept-source optical coherence tomography angiography in diabetic retinopathy. Issue 4 (21st December 2020) - Lu, Edward S; Cui, Ying; Le, Rongrong; Zhu, Ying; Wang, Jay C; Laíns, Inês; Katz, Raviv; Lu, Yifan; Zeng, Rebecca; Garg, Itika; Wu, David M; Eliott, Dean; et al.
Abstract : Aims: To compare the efficacy of diabetic retinal neovascularisation (NV) detection using the widefield swept-source optical coherence tomography angiography (WF SS-OCTA) vitreoretinal interface (VRI) Angio slab and SS-OCT VRI Structure slab. Methods: A prospective, observational study was performed at Massachusetts Eye and Ear from January 2019 to June 2020. Patients with proliferative diabetic retinopathy (PDR), patients with non-proliferative diabetic retinopathy and patients with diabetes but without diabetic retinopathy were included. All patients were imaged with WF SS-OCTA using the 12×12 mm Angio scan protocol centred on the fovea and optic disc. The en-face SS-OCTA VRI Angio slab and SS-OCT VRI Structure slab were evaluated for the presence or absence of NV. SS-OCTA B-scan was used to classify NV according to cross-sectional morphology (forward, tabletop or flat). All statistical analyses were performed using SPSS V.26.0. Results: One hundred and forty-two eyes of 89 participants were included in the study. VRI Angio detected NV at higher rates compared with VRI Structure (p<0.05). Combining VRI Angio and Structure improved detection rates compared with VRI Angio alone (p<0.05). Due to segmentation errors of the internal limiting membrane, NV with flat morphological classification had lower rates of detection on VRI Angio compared with NV with forward and tabletop morphology (p<0.05). Conclusions: WF SS-OCTA 12×12 mm VRI Angio and SS-OCT VRI Structure imaging centred on the fovea and optic disc detected NV with high sensitivity and low false positives. The VRI slab may be useful to diagnose and monitor PDR in clinical practice.